2020
DOI: 10.21037/atm-20-5741
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA suppresses ovarian cancer growth through inhibiting malignant properties and angiogenesis

Abstract: Background: In Chinese herbal medicine, Tanshinone IIA (Tan-IIA) is one of the main compounds extracted from Salvia miltiorrhiza Bunge. Tan-IIA has been demonstrated to inhibit the growth of various tumors. However, the detailed molecular and cellular mechanisms of the antitumor effect of Tan-IIA have yet to be fully illuminated.Methods: A2780 and ID-8 were treated with 0, 1.2, 2.4, 4.8, or 9.6 μg/mL Tan-IIA for 24 hours. Cell counting Kit-8 assay and EdU staining were used to evaluate cell proliferation. Term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Originally, danshen acted in cardiovascular and cerebrovascular diseases because it facilitates blood circulation and stasis clearance [27,28]. However, accumulating evidences have declaimed the additional efficacy of danshen in treating many types of cancer by its blockage of cancer growth and metastasis [18,20,22,[29][30][31][32][33][34][35][36]. In support of these pre-existing studies, our data reveal similar benefits of danshen for HNSCCs, cancers for which danshen's therapeutic effects have not been extensively investigated.…”
Section: Discussionsupporting
confidence: 79%
“…Originally, danshen acted in cardiovascular and cerebrovascular diseases because it facilitates blood circulation and stasis clearance [27,28]. However, accumulating evidences have declaimed the additional efficacy of danshen in treating many types of cancer by its blockage of cancer growth and metastasis [18,20,22,[29][30][31][32][33][34][35][36]. In support of these pre-existing studies, our data reveal similar benefits of danshen for HNSCCs, cancers for which danshen's therapeutic effects have not been extensively investigated.…”
Section: Discussionsupporting
confidence: 79%
“…THSWD combined with chemotherapy can effectively reduce serum VEGF levels and lymphatic vessel density in breast cancer patients, thereby blocking angiogenesis and inhibiting tumor growth and metastasis, but its mechanism of action is still unclear [ 80 , 81 ]. Existing clinical studies have also shown that THSWD can inhibit angiogenesis and endothelial cell proliferation, reduce tumor microvessel density, prevent the binding of VEGF and its receptor, and down-regulate serum MVD and VEGF-A in patients after surgery [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that tanshinone IIA has a growth inhibitory effect by inducing cell apoptosis and downregulating survivin expression in ovarian cancer cells ( Jiao and Wen, 2011 ; Li N. et al, 2018 ). Our studies showed that tanshinone IIA inhibits the growth of ovarian cancer cells in a dose-dependent manner by inducing G2/M phase arrest and cell apoptosis ( Zhou et al, 2020c ). In ovarian cancer, tanshinone IA significantly suppresses cell proliferation in vitro and tumor growth in vivo by inducing apoptosis and promoting autophagy via the inactivation of the PI3K/AKT/mTOR pathway in ovarian cancer ( Zhou et al, 2020a ).…”
Section: Tanshinones Inhibit Cell Proliferationmentioning
confidence: 88%
“…In ovarian cancer, Zhou et al found that tanshinone IIA inhibits the migration of A2780 and ID-8 ovarian cancer cells by inhibiting focal adhesion kinase phosphorylation ( Zhou et al, 2020c ). Another bioactive component, namely, cryptotanshinone, can suppress migration and invasion of ovarian cancer A2780 cells by dramatically inhibiting MMP-2 and MMP-9 expression ( Jiang et al, 2017 ).…”
Section: Tanshinones Block Metastasis Phenotypementioning
confidence: 99%